One Pathway Is Not Enough: The Cabbage Stem Flea Beetle Psylliodes chrysocephala Uses Multiple Strategies to Overcome the Glucosinolate-Myrosinase Defense in Its Host Plants - Beran, Franziska; Sporer, Theresa; Paetz, Christian; Ahn, Seung-Joon; Betzin, Franziska; Kunert, Grit; Shekhov, Anton; Vassão, Daniel G.; Bartram, Stefan; Lorenz, Sybille; Reichelt, Michael (Frontiers in Plant Science, 2018)
The cabbage stem flea beetle (Psylliodes chrysocephala) is a key pest of oilseed rape in Europe, and is specialized to feed on Brassicaceae plants armed with the glucosinolate-myrosinase defense system. Upon tissue damage, the β-thioglucosidase enzyme myrosinase hydrolyzes glucosinolates (GLS) to form toxic isothiocyanates (ITCs) which deter non-adapted herbivores. Here, we show that P. chrysocephala selectively sequester GLS from their host plants and store these throughout their life cycle. In addition, P. chrysocephala metabolize GLS to desulfo-GLS, which implies the evolution of GLS sulfatase activity in this specialist. To assess whether P. chrysocephala can largely prevent GLS hydrolysis in ingested plant tissue by sequestration and desulfation, we analyzed the metabolic fate of 4-methylsulfinylbutyl (4MSOB) GLS in adults. Surprisingly, intact and desulfo-GLS together accounted for the metabolic fate of only 26% of the total ingested GLS in P. chrysocephala, indicating that most ingested GLS are nevertheless activated by the plant myrosinase. The presence of 4MSOB-ITC and the corresponding nitrile in faeces extracts confirmed the activation of ingested GLS, but the detected amounts of unmetabolized ITCs were low. P. chrysocephala partially detoxifies ITCs by conjugation with glutathione via the conserved mercapturic acid pathway. In addition to known products of the mercapturic acid pathway, we identified two previously unknown cyclic metabolites derived from the cysteine-conjugate of 4MSOB-ITC. In summary, the cabbage stem flea beetle avoids ITC formation by specialized strategies, but also relies on and extends the conserved mercapturic acid pathway to prevent toxicity of formed ITCs.